2016
DOI: 10.1007/s10646-016-1687-x
|View full text |Cite
|
Sign up to set email alerts
|

Massive fish mortality and Cylindrospermopsis raciborskii bloom in Aleksandrovac Lake

Abstract: This paper presents a case study of a massive fish mortality during a Cylindrospermopsis raciborskii bloom in Aleksandrovac Lake, Serbia in mid-December 2012. According to a preliminary investigation of the samples taken on November 6 before the fish mortalities and to extended analyses of samples taken on November 15, no values of significant physicochemical parameters emerged to explain the cause(s) of the fish mortality. No industrial pollutants were apparent at this location, and results excluded the likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…in Greece and Russia (Kormas KA, Papadimitriou T, Chernova E: personal communications). An ongoing likelihood for the role of additional (or alternative) uncharacterised or novel cyanotoxins of health significance was provided in a further, major fish-kill in Serbia in which candidate cyanotoxins (CYN, STXs, MCs) were not detected although the C. raciborskii bloom material was lethal by bioassay using Artemia salina (Svirčev et al, 2016). It is evident that the range of health hazards presented by cyanobacteria and their metabolites is only partially understood.…”
Section: Fate Impact and Health Effectsmentioning
confidence: 99%
“…in Greece and Russia (Kormas KA, Papadimitriou T, Chernova E: personal communications). An ongoing likelihood for the role of additional (or alternative) uncharacterised or novel cyanotoxins of health significance was provided in a further, major fish-kill in Serbia in which candidate cyanotoxins (CYN, STXs, MCs) were not detected although the C. raciborskii bloom material was lethal by bioassay using Artemia salina (Svirčev et al, 2016). It is evident that the range of health hazards presented by cyanobacteria and their metabolites is only partially understood.…”
Section: Fate Impact and Health Effectsmentioning
confidence: 99%
“…However, the most common cyanotoxins (MCs, cylindrospermopsin, and saxitoxin) were not detected. It is possible that some other unknown or undetected toxic metabolites of this cyanobacterium were present and were a potential cause of the fish mortality in Aleksandrovac (Drobac, 2015;Svirčev et al, 2016a).…”
Section: Reservoirs Used For Irrigationmentioning
confidence: 99%
“…A preliminary attempt aimed at identifying the peptidic compounds has revealed that anabaenopeptins and cyanopeptolins were the most represented, but many other peptides are still to be structurally determined. As demonstrated by recent reports (Svirčev et al, 2016), the toxic potential of cyanobacteria can be only partially verified by current analytical techniques. Efforts to develop more comprehensive but specific methodologies are therefore still needed.…”
Section: Discussionmentioning
confidence: 96%